Patient‐ and physician‐reported radiation‐induced toxicity of short‐course radiotherapy with a prolonged interval to surgery for rectal cancer. (20th September 2022) - Verweij, Maaike E.; Hoendervangers, Sieske; von Hebel, Charlotte M.; Pronk, Apollo; Schiphorst, Anandi H. W.; Consten, Esther C. J.; Smits, Anke B.; Heikens, Joost T.; Verdaasdonk, Emiel G. G.; Rozema, Tom; Verkooijen, Helena M.; van Grevenstein, Wilhelmina M. U.; et al.
Abstract: Aim: A prolonged interval (>4 weeks) between short‐course radiotherapy (25 Gy in five fractions) (SCRT‐delay) and total mesorectal excision for rectal cancer has been associated with a decreased postoperative complication rate and offers the possibility of organ preservation in the case of a complete tumour response. This prospective cohort study systematically evaluated patient‐reported bowel dysfunction and physician‐reported radiation‐induced toxicity for 8 weeks following SCRT‐delay. Method: Patients who were referred for SCRT‐delay for intermediate risk, oligometastatic or locally advanced rectal cancer were included. Repeated measurements were done for patient‐reported bowel dysfunction (measured by the low anterior resection syndrome [LARS] questionnaire and categorized as no, minor or major LARS) and physician‐reported radiation‐induced toxicity (according to Common Terminology Criteria for Adverse Events version 4.0) before start of treatment (baseline), at completion of SCRT and 1, 2, 3, 4, 6 and 8 weeks thereafter. Results: Fifty‐one patients were included; 31 (61%) were men and the median age was 67 years (range 44–91). Patient‐reported bowel dysfunction and physician‐reported radiation‐induced toxicity peaked at weeks 1–2 after completion of SCRT and gradually declined thereafter. Major LARS was reported by 44 patients (92%) at some time during SCRT‐delay. Grade 3 radiation‐induced toxicity was reported in 17 patients (33%) and concerned predominantly diarrhoea. No Grade 4–5 radiation‐induced toxicity occurred. Conclusion: During SCRT‐delay, almost every patient experiences temporary mild–moderate radiation‐induced toxicity and major LARS, but life‐threatening toxicity is rare. SCRT‐delay is a safe alternative to SCRT‐direct surgery that should be proposed when counselling rectal cancer patients on neoadjuvant strategies.